A Sabbatical Journey of Discovery: The Liberation of Nursing - Mary Ferguson-Paré (Nursing Leadership, 2005)
This is the first in a series of reports to share key learnings from my sabbatical. In the spring and summer of this year I took a three-month journey through Scandinavia, Europe, Ireland and the United Kingdom to observe innovation in nursing service delivery and, in particular, nursing-led services; to explore outcome measurement as it relates to nursing services; to look at patient satisfaction and improving the patient experience as a form of outcome measurement; to learn about palliative care; and to examine ways in which different organizations, professional associations and policy-makers are attempting to move nursing care and healthcare services delivery into the future.